The more the better? Comparing two SQD-based learning designs in a teacher training on augmented and virtual reality - Josef Buchner; Martin Hofmann (International Journal of Educational Technology in Higher Education, 2022)
Abstract The purpose of this study was to investigate whether a learning design based entirely on the micro level strategies of the Synthesis of Qualitative Data (SQD) model is better suited to promote teachers augmented and virtual reality-related Will, Skill, and Tool (WST) compared to a learning design based less on the SQD model. To this end, we first developed two learning designs that were randomly distributed across two teacher professional development courses. In one course (n = 23), teachers learned according to our developed and fully SQD-based Tell–Show–Enact–Do (TSED) learning design; in the other course, teachers (n = 22) followed a Tell–Show–Enact (TSE) learning design that was less SQD-based. The results of the quasi-experimental field study show that the developed fully SQD-based TSED learning design is better able to promote the elements WST in teachers regarding the integration of augmented and virtual reality in the classroom. The results of the study have implications for theory and practice. For example, the developed TSED learning design can serve as a blueprint for other teacher educators, and the empirical findings support the micro level strategies recommended in the SQD model. Additional findings are discussed.